Caracterização dos atendimentos à pessoa idosa na atenção primária à saúde - Andres, Silvana Carloto (2022)
Population aging has become one of the greatest public health challenges. This was due to the increase in life expectancy and the insertion of new health technologies. Consequently, there is an increase in the demand for the improvement of public health policies and the restructuring of health care assistance for th is population. Thus, the objective of this study was to know the care provided by nurses and physicians to the elderly in primary health care (PHC). This is a descriptive field research, with a quantitative approach, through a questionnaire via the Google Forms platform. Nurses and doctors registered in their respective councils in the state of Rio Grande do Sul (RS) were included, and who have been working for at least six years. months in PHC with care for the elderly. Data were analyzed descriptively. Th e research had the participation of 65 doctors (41.7%) and 91 nurses (58.3%) who work in the area covered by the 4th Regional Health Coordination, in the state of RS. With this research, it was possible to know the profile of professionals and their perfor mance in PHC in the care of the elderly. The importance of correct understanding and use of the National Health Policy for the Elderly and Elderly Person's Health Handbook, the relevance of the team and multidisciplinary care, especially the joint action o f nurses and doctors in order to qualify the care provided, with due referral, when necessary and the importance of the companion to the elderly user during health care in order to have a better understanding between both parties.